Growth and reproductive aspects of white mullet, Mugil curema, in Lake Maracaibo, Venezuela - Ferrer Montaño, Orlando José; Villasmil, Leonidas (Ciencia)
A 5- year research study, including a 2- year mark- and- recapture program, was developed to estimate growth and reproductive aspects of white mullet, Mugil curema, in Lake Maracaibo. A single model did not fit the white mullet growth curve from juvenile stages to adult, but the re were two different segments: fish <130 mm total length (TL) grew at a rate of 0.359 mm/d and fish >130 mm TL grew at a rate of 0.232 mm/d. Parameters of the von Bertalanffy growth function for the growth phases were: LÂ¥ = 231 mm and k = 1.368 year-1 for fish <130 mm TL; LÂ¥ = 282 mm and k = 0.827 year-1 for fish >130 mm TL. The female: male proportion was 37:1. Mean length of immature females was 134.7 mm TL, and sexual maturity began at 200 mm TL for both sexes. Fecundity estimates ranged from 586,872 to 799,022 oocytes; fecundity correlated well with total length and body weight. Two lines of evidence suggested that white mullet in Lake Maracaibo is a multiple spawner: 1) Oocyte diameters differed among three designated zones of the ovary left lobe, and 2) Gonadosomatic index (GSI) values typical of heterochronal spawners; GSI values for ripe females ranged from 2.14 to 8.72%. In the light of these results, initiatives should be developed to protect coastal areas for white mullet in Lake Maracaibo.